ANALISIS PENGARUH LITERASI KEUANGAN, PENGGUNAAN TEKNOLOGI, INOVASI PRODUK, MODAL, DAN KUALITAS SDMTERHADAP KINERJA UMKM - Gading Adi Yoga Prayuda; Eny Kusumawati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to analyze the influence of financial literacy, technology utilization, product innovation, capital, and human resource (HR) quality on the performance of MSMEs in Madiun City. A descriptive quantitative approach with a survey method was employed, involving 99 MSME actors selected using Slovin's formula with a 10% margin of error from a population of 24,020 business units. Primary data were collected through an online questionnaire based on a five-point Likert scale. The dependent variable in this research is MSME performance, while the independent variables include financial literacy, technology utilization, product innovation, capital, and HR quality. Data analysis was conducted using multiple linear regression with SPSS 21. The results indicate that financial literacy, technology utilization, and capital have a significant positive influence on MSME performance. This means that better perceptions of these three aspects are associated with improved business performance. However, product innovation and HR quality do not significantly affect MSME performance. These findings suggest the importance of focusing on improving financial literacy, technology adoption, and access to business capital for enhancing MSME growth.